Connecting the Greenland ice-core and U∕Th timescales via cosmogenic radionuclides: testing the synchroneity of Dansgaard–Oeschger events - Adolphi, F; Ramsey, CB; Erhardt, T; Edwards, RL; Cheng, H; Turney, CSM; Cooper, A; Svensson, A; Rasmussen, SO; Fischer, H; Muscheler, R (Copernicus Publications, 2018)
During the last glacial period Northern Hemisphere climate was characterized by extreme and abrupt climate changes, so-called Dansgaard–Oeschger (DO) events. Most clearly observed as temperature changes in Greenland ice-core records, their climatic imprint was geographically widespread. However, the temporal relation between DO events in Greenland and other regions is uncertain due to the chronological uncertainties of each archive, limiting our ability to test hypotheses of synchronous change. In contrast, the assumption of direct synchrony of climate changes forms the basis of many timescales. Here, we use cosmogenic radionuclides (10Be, 36Cl, 14C) to link Greenland ice-core records to U∕Th-dated speleothems, quantify offsets between the two timescales, and improve their absolute dating back to 45 000 years ago. This approach allows us to test the assumption that DO events occurred synchronously between Greenland ice-core and tropical speleothem records with unprecedented precision. We find that the onset of DO events occurs within synchronization uncertainties in all investigated records. Importantly, we demonstrate that local discrepancies remain in the temporal development of rapid climate change for specific events and speleothems. These may either be related to the location of proxy records relative to the shifting atmospheric fronts or to underestimated U∕Th dating uncertainties. Our study thus highlights the potential for misleading interpretations of the Earth system when applying the common practice of climate wiggle matching.